Business research methods - Zikmund, William G.
This best-selling text continues in its ninth edition to provide the most current and comprehensive coverage of business research. Its student-friendly design contains numerous examples illustrating real-world research in management, marketing, finance, accounting, and other business areas. BUSINESS RESEARCH METHODS, 9E, is the ideal text for undergraduate and first year MBA courses in marketing, management, or quantitative studies.